2018
DOI: 10.1590/1678-4324-2016160288
|View full text |Cite
|
Sign up to set email alerts
|

Efficient In Vitro Somatic Embryogenesis and Plant Regeneration from Mature and Immature Embryos of Wheat ( Triticum aestivum L.)

Abstract: An efficient regeneration system is a pre-requisite for the application of genetic transformation and functional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Conditions promising for callogenesis and regeneration of one genotype are not always conducive for another genotype of the same species. 54 , 55 Hence, wheat genotypes differ for callus induction and regeneration potential, and almost immature embryo of all genotypes had the potential of callogenesis to some extent. 11 , 14 , 55 We employed two wheat genotypes (AS-2002 and Wafaq-2001) and observed that the genotypes differ for tissue culture responses especially for embryogenic callus induction and regeneration in response to media supplemented with various combination of growth regulators ( Figs 4and5 &),CuSO 4 , AgNO 3 and their nano particles ( Tables 2, 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions promising for callogenesis and regeneration of one genotype are not always conducive for another genotype of the same species. 54 , 55 Hence, wheat genotypes differ for callus induction and regeneration potential, and almost immature embryo of all genotypes had the potential of callogenesis to some extent. 11 , 14 , 55 We employed two wheat genotypes (AS-2002 and Wafaq-2001) and observed that the genotypes differ for tissue culture responses especially for embryogenic callus induction and regeneration in response to media supplemented with various combination of growth regulators ( Figs 4and5 &),CuSO 4 , AgNO 3 and their nano particles ( Tables 2, 3 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 Hence, wheat genotypes differ for callus induction and regeneration potential, and almost immature embryo of all genotypes had the potential of callogenesis to some extent. 11 , 14 , 55 We employed two wheat genotypes (AS-2002 and Wafaq-2001) and observed that the genotypes differ for tissue culture responses especially for embryogenic callus induction and regeneration in response to media supplemented with various combination of growth regulators ( Figs 4and5 &),CuSO 4 , AgNO 3 and their nano particles ( Tables 2, 3 and 4 ). It is likely that tissue culture responses of genotypes might vary due to dissimilar cytoplasmic composition and gene action.…”
Section: Discussionmentioning
confidence: 99%
“…2,4-D efficiently stimulates cell division, plant growth and in vitro-induced morphogenetic responses at low concentrations of 1-10 mg/L, while spraying the plants in the field with 2,4-D of a concentration of about one-thousand-fold higher (2 g/L, according to the weed control manuals) caused lethal symptoms that were similar to an auxin overdose [9]. Of note, in spite of the distinctly higher tolerance of the monocot vs. the dicot plants to the toxic effects of 2,4-D [10], similar concentrations of this substance are applied to induce SE in different plants, and relevantly, 1-2 mg/L of 2,4-D is recommended for SE induction in maize and wheat [11][12][13][14], while 1.1 mg/L of 2,4-D is effective for establishing an embryogenic culture in Arabidopsis [15].…”
Section: Auxin-and Stressor-like Activity Of 24-d In Se Inductionmentioning
confidence: 99%
“…On the other hands, Kin was more than effective in callus induction from the leaf explants of M. azedarach L. However, in in orescence explant, the callus induction in all assayed PGR combinations, except 1 mg/L NAA + 1 mg/L BAP (63.89%), was higher than 87.83%; but callus growth (fresh weight) in this explant was lower than that of the leaf explant. It has been proven that the optimal PGRs combination for callus induction and growth is varied depending on the plant species, genotype and explant type, and should be experimentally optimized (Zare et al, 2009;Ahmadpour et al 2016;Mostafa et al 2020). In our study, the calli produced from M. azedarach L. leaf explants exhibited a great growth and biomass, and produced higher than 5 g fresh weight per explant on MS medium supplemented with 5 mg/L NAA + 3 mg/L Kin and 5 mg/L NAA + 5 mg/L BAP.…”
Section: Discussionmentioning
confidence: 99%
“…practicable way to plant regeneration, cell suspension culture and production of secondary metabolites(Ahmadpour et al 2016;Firoozi et al 2019). Different factors including plant growth regulators especially auxins and cytokinins, plant genotype and explant type in uence the callus induction, cell growth and development, and secondary metabolites production in the plant cells(Zare et al, 2009;Firoozi et al, 2019;Farjaminezhad and Garoosi, 2019) In the present study, we investigated the effect of different PGRs combinations including auxins (NAA and 2,4-D) and cytokinins (Kin and BAP) on callus induction and growth, and cell suspension culture establishment, growth and secondary metabolites production from leaf, in orescence and petiole explants of M. azedarach L. The percentage of callus induction, callus growth (biomass), color and texture of the calli were different depending on the M. azedarach L. explant type and applied PGRs combinations.…”
mentioning
confidence: 99%